Model Mind Mapping Berbantuan Media Roda Putar Untuk Meningkatkan Berpikir Kreatif Siswa Sekolah Dasar - Nova Amalia Ulfa; Fina Fakhriyah; Much Arsyad Fardhani (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
The purpose of this study is to find out the application of Mind Mapping learning model assisted by the rotary wheel media to improve the creative thinking of fourth grade students of elementary schools. The research was conducted in the classroom action research with research subjects of fourth grade students with total of 15 students. This classroom action research would take place in two cycles, namely cycle 1 and cycle 2 in the theme 6 of My Ideals. The dependent variable in this study is students’ creative thinking, while the independent variables are the Mind Mapping learning model with the rotary wheel media.  The data collection techniques of this study were test and non-test. Data analysis techniques used qualitative and quantitative data analiysis. The result of this study showed the improvement in students’ creative thinking skill. This is evidenced by the average percentage at the pre-cycle stage, a percentage of 40% was obtained with uncreative criteria, then increase in the first cycle increased to 73.33% with quite creative criteria and in the second cycle increased to 86.67% with creative criteria. Based on the result, it concluded that the application of Mind Mapping learning models can improve fourth grade students’ creative thinking.